Analysis Method for the Mass Center of Low Earth Orbit Remote Sensing in Orbit - Jinghao, Xu; Wenjing, Ding; Lei, Zhang; Zhilong, Zhang (Journal of physics. Conference series, 2021)
A real-time method for estimating the mass center of low earth orbit (LEO) remote sensing satellite in orbit is introduced in this paper. LEO remote sensing satellite requires highly on calculating the position of its mass center, due to the need of precise orbit determination and attitude control. This article offers an analysis method for the factors that play a leading role in the change of the centroid of satellite in orbit, which are the consuming of satellite fuel, the circulation of satellite-to-ground data transmission antenna and rotation of solar arrays. The parameters for calculating the centroid of LEO remote sensing satellite are defined, and a formula for computing the position of the satellite mass center in orbit is proposed.